Rice Export Situation in Savannakhet Province - SOMBOUNSAK, Phoumsaydavone; XAYYALATH, Kaysone (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The study of rice export situation in Savannakhet Province has three objectives: 1. To explain rice export situation in Savannakhet Province, 2. To assess capability of rice export in Savannakhet Province, and 3. To analyze factors affecting rice exports in Savannakhet Province. This study used a monthly data from 2015-2018. It is a comparative analysis of the yearly import and export conversion figures, to explain the overview and analyze export advantages, comparative analyzed of constant market share of import and export between province to the country. Compare the value rice export of Laos with that of others, testing the economic factors that affect the value of exports through a regression. Capability analysis of export shown that revealed comparative advantage of rice export from Savannakhet province to China was greater than 1 it means that Savannakhet was advantageous in export rice to China. Constant market share analysis found that factor of expand market and factor of competitive capability were reflexing to changing of rice export value were 314,938,540 and 5,478,972 respectively. The study on factors effecting to rice export of Savannakhet province found that quantity of rice export, price index of food consumption and rate inflation of total exchange were associated to each variable with 94% and all of three variables can explain rice export value by R= 88% and F= 44.33, p-value= 0.000 means that by 95% of significant level the equation can be used.